1993
DOI: 10.1007/bf02542583
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar properties of lipase fromCandida parapsilosis (Ashford) langeron and talice

Abstract: A new Candida parapsilosis lipase was isolated and studied. This enzyme was purified by hydrophobic chromatography on a phenyl-sepharose CIAB column followed by gel permeation on a Sephacryl $300 HR column. It was a 160 kg'mo1-1 molecular-weight oligomeric enzyme. Optimal activity was obtained at 45°C and pH 6.5. The lipase activity toward various acylglycerols and esters was studied. The hydrolysis rate was greater for secondary acylesters than for primary acylesters. This lipase showed a high specificity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…Within the few lipases able to catalyze alcoholysis preferentially to hydrolysis in aqueous media, the lipase/acyltransferase CpLIP2 from C. parapsilosis appears as the best candidate today for the development of lipid bioconversions and functionalizations without a strict control of a w [14,19,23] and has been described as of high industrial interest [41][42][43][44]. With CpLIP2, competition of a short chain alcohol with water has been shown to be highly favorable to the alcohol, even with a high a w and a low thermodynamic activity of the alcohol [9,14,18,21,23]. Transesterification with this enzyme appears thus kinetically controlled (very low rate of hydrolysis versus high rate of alcoholysis), which allows the production of new esters at concentrations above the thermodynamic equilibrium of hydrolysis/esterification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the few lipases able to catalyze alcoholysis preferentially to hydrolysis in aqueous media, the lipase/acyltransferase CpLIP2 from C. parapsilosis appears as the best candidate today for the development of lipid bioconversions and functionalizations without a strict control of a w [14,19,23] and has been described as of high industrial interest [41][42][43][44]. With CpLIP2, competition of a short chain alcohol with water has been shown to be highly favorable to the alcohol, even with a high a w and a low thermodynamic activity of the alcohol [9,14,18,21,23]. Transesterification with this enzyme appears thus kinetically controlled (very low rate of hydrolysis versus high rate of alcoholysis), which allows the production of new esters at concentrations above the thermodynamic equilibrium of hydrolysis/esterification.…”
Section: Introductionmentioning
confidence: 99%
“…Such enzymes and their applications have been described for several years by our group. The first one was the CpLIP2 lipase/acyltransferase from Candida parapsilosis [17][18][19][20][21], followed by CaLIP4 from Candida albicans [22] and CtroL4 from Candida tropicalis [23]. These lipases/acyltransferases have been shown to be homologous to C. albicans lipase 1 and CAL-A, the lipase A of P. antarctica (formerly designated as Candida antarctica) [20,24] and to belong to the P. antarctica lipase A-like α/β hydrolase superfamily (abH38) [23,25,26] of the Lipase Engineering Database [27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is known that the polyunsaturated fatty acids in natural oils are generally located on a glycerol internal position. 3) Riaublanc (1993) studied the hydrolysis activity of Candida parapsilosis in various homogeneous acylglycerols and esters. He demonstrated that the specificity of hydrolysis activity increased with the degree of fatty acid unsaturation.…”
Section: Resultsmentioning
confidence: 99%
“…This was not observed during the transfer reactions catalysed by the free lipase from Candida cylindracea, when the transesterification kinetics increased with the substrate or enzyme hydration until saturation of the phases (Goldberg CT al., 1990). This paper describes alcoholysis of rapeseed oil by methanol, catalysed by the lipase from ('nndida parnpsilosis described by Riaublanc (1993) in a biphasic liquid/liquid medium consisting of a lipid emulsion in an aqueous medium containing free enzyme and alcohol in solution.…”
mentioning
confidence: 99%
“…It can therefore tentatively be concluded that CALA and all the staphylococcal lipases tested hydrolyse triolein in the sn-2 position. In a previous study, Riaublanc et al [51] reported that a lipase from Candida parapsilosis (Ashford) hydrolysed secondary acylesters faster than primary acylesters. When rapeseed oil was used as the substrate, similar amounts of 1,2(2,3) and 1,3 diacylacylglycerol were measured by these authors.…”
Section: The Sn-2 Preference Of Lipasesmentioning
confidence: 98%